The Effect of Aloe Vera Pudding (Aloe vera L.) and Dragon Fruit Pudding (Hylocereus polyrhizus) on Blood Glucose Levels in Patients with Diabetes Mellitus - ANGGUN JUNISA; Dwi Kurnia Purnamasari (Jurnal Andaliman: Jurnal Gizi Pangan, Klinik dan Masyarakat, 2026)
Diabetes mellitus (DM) is a chronic metabolic disease characterised by persistent hyperglycaemia resulting from impaired insulin production or action. Non-pharmacological management through natural functional foods continues to gain attention, including the use of aloe vera and red dragon fruit. This study aimed to determine the effect of aloe vera pudding and dragon fruit pudding on blood glucose levels in DM patients within the working area of Semanding Public Health Centre, Tuban Regency. A true experimental design with a two-group pre-test and post-test approach was employed. Twenty adult DM patients were selected by purposive sampling and assigned equally to two groups. Group one consumed aloe vera pudding (250 g/day) and group two consumed dragon fruit pudding (250 g/day) for seven consecutive days. Blood glucose was measured before and after the intervention using a glucometer. Data were analysed using the Paired T-Test and Independent T-Test. Results showed that aloe vera pudding significantly reduced blood glucose (p=0.027), and dragon fruit pudding likewise (p=0.001). However, the comparison between groups revealed no statistically significant difference (p=0.374). Both puddings are therefore considered potential complementary therapies for glycaemic control in DM patients.